Refining English language tests for university admission: a Malaysian example / Arshad Abd Samad, Sharifah Zainab Syed Abd Rahman, and Siti Norbaiti - Abd Samad, Arshad (ACRULeT, Faculty of Education & UiTM Press, 2008)
English has now become the lingua franca of much of technological, business and academic endeavours. Consequently, learning the English language is now seen as vital, especially at the university level where proficiency in the language has become a selection criterion. At present, the Malaysian University English Test (MUET) has been adopted by Malaysian public universities as an indicator of English language proficiency. A student’s overall result depends on all the four language components of the MUET and often determines the number and nature of the English language courses he or she has to attend at university. This study seeks to examine whether MUET is an accurate predictor of performance and success at university and how the MUET can be finetuned as an entry level English language test. It was carried out among 52 third year undergraduates of the Faculty of Educational Studies, Universiti Putra Malaysia, Serdang, Malaysia, admitted into the Teaching English as a Second Language (TESL) programme. The findings of the study do not offer conclusive evidence about the validity of MUET as a predictor of academic success. However, six models of various combinations of scores on language components on the MUET scores are examined in terms of their effectiveness in increasing the accuracy in selecting students for the TESL programme. The correlations obtained using these models indicate that the combination of various components of the MUET can be used to more accurately predict student achievement at tertiary level than the cumulative MUET score itself. The results of these correlations and their implications in using language tests as admission requirements in general are also discussed.